Investigation of optimal sperm storage conditions for short-term storage (Bangladesh Journal of Medical Science, 2024)
Objective The quality of sperm cells is important role in the success rates of assisted reproduction technology (ART) treatments. The quality of the sperm cells shows variations depending on the temperature of short-term semen storage as well as the methods of semen preparation. Thus, this study aimed to investigate the sperm viability, motility and DNA fragmentation following different sperm preparation methods and short-term storage conditions, respectively. Materials and Methods A total of 25 semen samples were evaluated. In the first part of this study, different incubation temperatures were investigated in two groups, in such the first group involved the semen samples and the second group involved the sperm cells separated by density gradient centrifugation method, respectively. The samples in each group were incubated at 4°C, room temperature (21°C) and 37°C for 24 hours, respectively. The sperm cell qualities were evaluated by mobility analysis, DNA fragmentation by acridine orange staining and sperm cell viability by propidium iodide staining. Results and Discussion The analysis outcome demonstrated that the mobility, DNA fragmentation and viability of the sperm cells were statistically different when incubated at RT (21°C) in both groups. Furthermore, samples prepared by the density gradient centrifugation method were shown to have better quality. The optimum short-term storage temperature was detected to be the room temperature. Conclusion The conclusion of this investigation is crucial to assess storage conditions in ART clinics. This study provides essential data for short-term sperm storage and preparation methods to improve the success rates of ART clinics.Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1137-1141